Incidence and etiology of mandibular fractures treated in Vilnius University Hospital Žalgiris clinic, Lithuania: a review of 1 508 cases - Zaleckas, Linas; Drobnys, Povilas; Rimkuvienė, Jūratė (Acta medica Lituanica, 2013)
Relevance of the study: this is the first Lithuanian study, which analyzes in detail the incidence, etiology and circumstances of mandibular fractures treated in the Vilnius University Hospital, Lithuania. The data and findings of this study are compared with other studies, identifying specific mandibular trauma patterns in Lithuania. Background. During past few decades, the socioeconomic situation in Lithuania has been changing significantly, and there is a need to evaluate data about mandibular fracture epidemiology and etiology. The aim of the study was to analyse the incidence, etiology, circumstances and localization of mandibular fractures treated in the Department of Oral and Maxillofacial Surgery, Vilnius University Hospital Žalgiris Clinic, Lithuania. Materials and methods. The medical records of 1 508 patients with mandibular fractures, treated between 1 January 2005 and 31 December 2009, were reviewed. The following data were analysed: age, gender, trauma date and time, etiology and circumstances of trauma, fracture area. Results. The male : female ratio was 7.3 : 1. The majority of patients (53.6%) were young people, aged 16–30 years. Mandibular fractures most often (53%) occurred between May and September, mostly at weekends (61%) and in the late evening (60%). The main cause of mandibular fractures was interpersonal violence (70%), followed by falls and accidents (19%), and road traffic accidents (6%). Even 15% of men and 10% of women were alcohol intoxicated at the time of trauma. The most common fracture area was mandibular angle (32%) and condylar process fractures (31%). Conclusions. The incidence of mandibular fractures was remarkably larger in the male, during the second and third decade of life. Most mandibular fractures occurred in the warm period of the year, especially at weekends and late evening. The mandibular basis region was the most common fracture site. The most common cause of mandibular fractures was assault.